INOVASI PEMBELAJARAN IPAS: PENGGUNAAN MEDIA AUDIOVISUAL PADA MATERI NORMA DALAM ADAT ISTIADAT DAERAHKU DI MI ISLAMIYAH 01 MADIUN - Melik Budiarti; Ratih Indriana Yuliati; Novia Karisma Putri; Ema Fitriana Chayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study addresses the low learning outcomes of fourth-grade students at MI Islamiyah 01 Madiun in the subject of Social Sciences (IPAS), specifically on the topic of "Norms in My Local Customs." The purpose of this research is to examine the use of audiovisual media in improving students' learning outcomes on this material. The study employs a classroom action research (CAR) approach conducted in two cycles involving 23 students. Data were collected through observation, documentation, and pretest-posttest assessments. In the first cycle, the use of audiovisual media showed initial improvements in student engagement and understanding, although some students still scored below the minimum mastery criteria. After refining the audiovisual media and learning strategies in the second cycle, there was a significant increase in the number of students achieving scores above the minimum mastery criteria, along with enhanced participation and motivation during the learning process. These findings indicate that integrating audiovisual media in IPAS learning not only improves cognitive outcomes but also fosters positive attitudes and active student involvement. The study concludes that audiovisual media is an effective tool to enhance learning outcomes on abstract and contextual topics such as norms and local customs, and recommends broader application in similar educational contexts.